Konvergensi dan Manajemen SDM Media Lokal - Fatimah Sari (Jurnal Komunikasi, 2022)
Technological developments also affect the media industry, namely journalistic and editorial management practices, to affect human resource management. The impact of media convergence on human resources is the increasing workload of journalists and the increasing qualification of HR recruitment in the form of understanding technological advances. This research aims to find out the policy of media convergence in bringing changes to the human resource management process of Lahat Pos Group, one of the local media organizations in South Sumatera Province, Indonesia. This research uses qualitative descriptive approach methods. Data collection techniques are in-depth interviews and in-person observation. Based on the study results, Lahat Pos Group uses the newsroom 3.0 model; the newsgathering and news writing process are convergent, namely, in Lahat Pos Group, one management and one newsroom. In Lahat Pos Group analysis and classification are not used due to the absence of significant differences. The recruitment stage of Lahat Pos Group continues to use the means of tests, selection, interviews, training, and internships until journalists get an assessment to be a benchmark for compensation to be received.